Unconfined silane-air explosions. (September 2017) - Tsai, Hsiao-Yun; Lin, Yu-Jhen; Chang, Yan-Cheng; Lin, Jyun-Sian; Chen, Jenq-Renn; Ngai, Eugene Y.
Abstract: In the present work, field experiments on unconfined explosions of silane-air mixture were performed by utilizing a cubic frame covered with a thin vinyl film for release confinement and a sufficiently high release velocity of silane from a tube to prevent ignition. The silane release was controlled by a mass flow controller such that the amount before the ignition can be accurately controlled. Ignition from the tube exit locating at the center of cubic frame was initiated by shutting off the silane flow. To control precisely the final concentration in the cube, air in the cube was pumped out to the exact amount of silane feed in prior to feeding silane. High-speed video camera and pressure sensors were used to record the blast wave and flame propagation. Experiments on a wide range of silane concentration and total silane mass were performed. Finally, the unconfined gas explosion models by Dorofeev (1996) and the acoustical theory for expanding flame by Thomas and Williams (1966) are used to predict the overpressure from the recorded flame histories. Recommendations are made regarding the worst case modeling of silane release and explosion. Highlights: Field experiments on unconfined explosions of silane-air mixtures are performed. A cubic chamber consisting of a metal frame covered with a thin clear vinyl film for confinement was used. Special efforts were made to ensure a good mixing and accurate control of silane concentration in the chamber. A high-speed video camera and pressure sensors were used to record the blast wave and flame propagation. Recommendations are made regarding the worst case modeling of silane release and explosion.